Pengaruh Moral Pajak dan Kepercayaan Terhadap Pemerintah Terhadap Kepatuhan Wajib Pajak UMKM Kota Palembang - Angelica Febiola Leonardus; Kathryn Sugara (MDP Student Conference, 2026)
This study analyzes the influence of tax morality and trust in the government on the tax compliance of Micro, Small, and Medium Enterprises (MSMEs) taxpayers in Palembang City. The research method used is quantitative and associative. Data collection was carried out by distributing 157 questionnaires to MSME taxpayers in Palembang City using purposive sampling. Data analysis was carried out using multiple linear regression, after the instrument met the tests of validity, reliability, and classical assumptions. The results of the study show that tax morality and trust in the government affect tax compliance both partially and simultaneously. The value of the determination coefficient with a value of 68.4% shows that the variation in MSME tax compliance can be explained by the combination of two independent variables in the research model. These findings confirm that MSME tax compliance is influenced by tax morality and trust in the government.